PENGARUH DEASETILASI DAN ALKALINASI TERHADAP KARAKTERISTIK KARBOKSIMETIL KITOSAN - Yusro Nuri Fawzya; Rina Novianty; Singgih Wibowo (Universitas Gadjah Mada, 2008)
Carboxymethyl chitosan (CMCts) is one of the chitosan derivatives produced by the carboxymethylation process of chitosan. Compared to chitosan which is soluble in weak acid, the CMCts is soluble in water and it becomes more desirable in many applications both in pharmaceutical and food industries. Chitosan as the raw material of CMCts was made from chitin deacetylation. The reasearch aimed to study the effect of chitin deacetylation methods and concentrations of sodium hydroxide in the alkalination process on the characteristics of CMCts produced. Three deacetylation processes were applied in the production of chitosan, i.e. treatment with 60% NaOH at 70oC for 2 and 3 days, and treatment with 60% NaOH at ambient for 5 days. Whereas, the alkalination process was conducted using NaOH at the concentrations of 20, 30, 40 and 50%. The carboxymethylation of chitosan was carried out using monochloroacetic acid with the ratio of chitosan to monochloroacetic acid of 1 : 1.5 (w/w) at 50oC for an hour. The results showed that the CMCts produced had solubilitiy of 27.0 to 98,1% and viscosity of 28 to 265 cPs. Based on the solubility and viscosity, the best treatment was found on using chitosan which had been deacetylated with 60% NaOH at 70oC for 3 days followed by alkalination using NaOH of 30% before carboxymethylation. The treatment resulted CMCts with water solubility 98.1%, viscosity 265 cPs and yield 72.2%.